2007
DOI: 10.1371/journal.pgen.0030028
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Loading of Cohesin Subunits during the First Meiotic Prophase of Grasshoppers

Abstract: The cohesin complexes play a key role in chromosome segregation during both mitosis and meiosis. They establish sister chromatid cohesion between duplicating DNA molecules during S-phase, but they also have an important role during postreplicative double-strand break repair in mitosis, as well as during recombination between homologous chromosomes in meiosis. An additional function in meiosis is related to the sister kinetochore cohesion, so they can be pulled by microtubules to the same pole at anaphase I. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 64 publications
1
22
0
Order By: Relevance
“…Then, only the non-centromeric chromosomal regions, those which have previously developed cohesin axes and loaded the meiotic recombination machinery, will be able to achieve pairing and synapsis. However, DSBs could occur concomitantly with the axis formation (van Heemst and Heyting 2000;Kleckner 2006;Lorenz and Whitby 2006;Sánchez-Morán et al 2007). Consequently, although synapsis is severely reduced, SC is always formed at the non-centromeric ends of each autosome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, only the non-centromeric chromosomal regions, those which have previously developed cohesin axes and loaded the meiotic recombination machinery, will be able to achieve pairing and synapsis. However, DSBs could occur concomitantly with the axis formation (van Heemst and Heyting 2000;Kleckner 2006;Lorenz and Whitby 2006;Sánchez-Morán et al 2007). Consequently, although synapsis is severely reduced, SC is always formed at the non-centromeric ends of each autosome.…”
Section: Discussionmentioning
confidence: 99%
“…In order to establish accurately the pattern of synapsis progression in P. meridionalis, we have used, as in previous studies of other orthopteran species (Viera et al 2004a, b;Calvente et al 2005;Valdeolmillos et al 2007), antibodies against SMC3, which is widely conserved in eukaryotes (Hirano 2002). We have also analysed the dynamics of another cohesin subunit, SMC1α.…”
Section: Cohesin Axis Maturation As a Marker For Synapsis Progressionmentioning
confidence: 99%
“…Exchange is apparent from images of chiasmata in diplotene chromosomes, which further show that sister chromatid axes are locally separated at these sites (see picture in Jones and Franklin 2006). Indeed, certain axial structural components, including cohesins, are already known to be specifically absent from chiasmata sites; e.g., Rec8 in mouse (Eijpe et al 2003) and MCD1/SCC1/ RAD21 plus SMC3 in grasshoppers (Valdeolmillos et al 2007). Occurrence of axis changes being specific to sites of COs, it would be sensible for these local axis changes to begin at the time of CO designation, thus much earlier than when observed at chiasmata sites during diplotene, and then to proceed in concert with the DNA events of recombination (e.g., Blat et al 2002).…”
Section: Proposed Biological Significance Of Co-directed Local Axis Dmentioning
confidence: 95%
“…Here, this situation has been circumvented by using antibodies generated against the cohesin subunits, SMC3 and SMC1α. The analysis of the SMC3 cohesin axes throughout prophase I has allowed the identification of the different stages in several insect species (Calvente et al 2005;Valdeolmillos et al 2007;Viera et al 2004aViera et al , b, 2009b. In this sense, we have previously shown that, in squashed pachytene spermatocytes of G. italicum, SMC3 appears along axes of both autosomes and sex chromosomes (Page et al 2006), and it has also been reported that the cohesin axes reflect the position of the underlying axial elements/lateral elements (AEs/LEs ; Pelttari et al 2001;Viera et al 2004b).…”
Section: The Cohesin Axes As Markers For Synapsis Progressionmentioning
confidence: 99%